2017
DOI: 10.1016/j.egja.2017.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Superficial parotidectomy under local anesthesia, case report

Abstract: a b s t r a c tFor superficial parotidectomy general anesthesia is ideal, but certain patients may be unfit. The present case had uncontrolled hypertension together with difficult airway. To avoid any suspected complications, we decided to do the operation under local anesthesia. We planned to block the maxillary nerve and superficial cervical plexus with greater auricular nerve together with incision site infiltration. A mixture of bupivacaine 0.25% and lignocaine 1% with adrenaline 1: 200,000 was prepared. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…In Group S, the time of first analgesia request was 10.40 ± 2.41 h. Previous studies using SCPB in parotid surgery did not declare the duration to the first analgesia request [ [1] , [2] , [3] ]. However, Yaho et al [ 27 ] showed that the first analgesic request following SCPB was 18 h in thyroid surgery , as they used higher concentration of LA 10 ml ropivacaine 0.5% [ 27 ].…”
Section: Discussionmentioning
confidence: 95%
“…In Group S, the time of first analgesia request was 10.40 ± 2.41 h. Previous studies using SCPB in parotid surgery did not declare the duration to the first analgesia request [ [1] , [2] , [3] ]. However, Yaho et al [ 27 ] showed that the first analgesic request following SCPB was 18 h in thyroid surgery , as they used higher concentration of LA 10 ml ropivacaine 0.5% [ 27 ].…”
Section: Discussionmentioning
confidence: 95%